STABLE UNION AND DATING CONTRACT WITHIN THE CONTEXT OF BRAZILIAN FAMILY LAW (REMUNOM, 2024)
Currently, a large part of Brazilian society believes that the establishment of a lasting relationship is enough to characterize a stable union. However, with legislative changes, the main requirement for the institute to be recognized became the shared and current intention of founding a family life. In this sense, article 1,173 of the 2002 Brazilian Civil Code covers the necessary requirements for identifying a stable union, which are: public, continuous coexistence with the purpose of building a family.Therefore, in a relationship in which there is no desire to start a family, or in which the intention is only for the future, there is nothing to talk about in a stable union, since the main qualification for setting up the institute does not exist. However, according to the expression used by the doctrine and also by a collegiate decision of the STJ, it can be called "qualified dating", which may be protected by the dating contract. That said, this article aims to discuss the differences between these two institutes, addressing their main aspects and characteristics, as well as their applicability in Brazilian jurisdiction.